Hubungan Perilaku Hidup Bersih Sehat dan Sanitasi Lingkungan Terhadap Kejadian Penyakit Scabies - Boraa, Irgi Dimas; Taeteti, Anna Mariance; Anugerah, Muslimah (JURNAL NERS LENTERA, 2023)
Scabies is an itchy disease caused by mites or lice that cause rashes and redness on the skin and it affects communities that lack hygiene. Conducting PHBS at home is an effort to empower household members to know, be able and willing to practice clean and healthy life behaviors. Environmental sanitation is a public health effort to maintain and monitor environmental factors that can affect health status.  This study is to determine the relationship between clean and healthy life behavior (PHBS) and environmental sanitation with the incidence of scabies disease in the Pariti Community Health Center Working Area, Sulamu Subdistrict, Kupang Regency. This study used quantitative method by using a cross sectional research design. The number of samples was 58 respondents using sampling techniques, analysis using Rank Spearman. The Spearman Rank correlation test showed that the PHBS and environmental sanitation factors were associated with scabies where the significant value (p) was 0.000>α=0.05. There was a relationship between Clean and Healthy Life Behavior and Environmental Sanitation with the Incidence of Scabies Disease in the Pariti Community Health Center Working Area, Sulamu Subdistrict, Kupang.